External and internal load of playing positions of elite female handball players (U19) during competitive matches - Belka, J.; Hulka, K.; Safar, M.; Weisser, R. (Acta Gymnica, 2016)
Background: Effective training depends on knowledge of the sport's requirements. Physical (external load) and physiological (internal load) analyses will provide valuable data that can be used for other research and to improve specific training requirements. Handball is an intermittent sport game, and it is important discover the factors, that affect the performance in a handball match.